2022
DOI: 10.1363/psrh.12213
|View full text |Cite
|
Sign up to set email alerts
|

Disruptions and opportunities in sexual and reproductive health care: How COVID‐19 impacted service provision in three US states

Abstract: Context The COVID‐19 pandemic abruptly disrupted the provision of sexual and reproductive health care in the United States. Methods We conducted interviews with family planning clinic staff at 55 health care facilities in Arizona, Iowa, and Wisconsin in late 2020 and early 2021. We asked respondents about the challenges they faced and ways they adapted their service provision as a result of the pandemic. We conducted content and thematic analyses of the interview transcripts using an inductively developed qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Research from other facilities across the US showed similar adaptations, with providers using telemedicine, replacing in-clinic ultrasounds with at-home pregnancy tests, and distributing medication abortion drugs via curbside pickup or mailing. 12,59 While facilities in these three states were not able to take full advantage of the US FDA's temporary lifting of the in-person dispensing requirement of Mifepristone Risk Evaluation and Mitigation Strategy (REMS) Program, 60 a move toward telemedicine appointments for pre-abortion counseling, medication information dissemination, and post-abortion care could add needed flexibility in scheduling and managing patient volume during emergencies such as the pandemic or rapid policy changes such as those following Dobbs. While the FDA later announced that it would permanently lift the in-person dispensing requirement for mifepristone, 61 full telemedicine for abortion remains unavailable to patients in this region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research from other facilities across the US showed similar adaptations, with providers using telemedicine, replacing in-clinic ultrasounds with at-home pregnancy tests, and distributing medication abortion drugs via curbside pickup or mailing. 12,59 While facilities in these three states were not able to take full advantage of the US FDA's temporary lifting of the in-person dispensing requirement of Mifepristone Risk Evaluation and Mitigation Strategy (REMS) Program, 60 a move toward telemedicine appointments for pre-abortion counseling, medication information dissemination, and post-abortion care could add needed flexibility in scheduling and managing patient volume during emergencies such as the pandemic or rapid policy changes such as those following Dobbs. While the FDA later announced that it would permanently lift the in-person dispensing requirement for mifepristone, 61 full telemedicine for abortion remains unavailable to patients in this region.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, facilities in these states adapted their service delivery in part based on public health guidance. Research from other facilities across the US showed similar adaptations, with providers using telemedicine, replacing in‐clinic ultrasounds with at‐home pregnancy tests, and distributing medication abortion drugs via curbside pickup or mailing 12,59 …”
Section: Discussionmentioning
confidence: 99%
“…According to the World Health Organization (WHO), 4.3 billion people of reproductive age worldwide will not have access to at least one SRH intervention in their lifetime [1]. More recently, the COVID-19 pandemic has significantly impacted the provision of these services [2][3][4][5][6][7][8][9]. Fear of accessing in-person care, medication shortage, suspended services and care programs have limited access to SRH services during the pandemic [2,3,8].…”
Section: Introductionmentioning
confidence: 99%